Reflections on Curiosity - van Bemmel, J. H. (Yearbook of Medical Informatics, 2008)
Objective The purpose of this article is to show that curiosity is the driving force behind all scientific endeavors. The second purpose is to show that all science is constrained on its underlying assumptions.Methods Three examples are used to illustrate the above theses: one from cosmology, the second from biomedical research, and the third from the formalization of human reasoning in a computer. The three examples are supported by quotes from Albert Einstein [1].Results and conclusionsResearch in cosmology shows that the horizon of our knowledge is continuously expanding but that major scientific questions remain to be solved. The second example from biomedicine explains that the more we discover of the details of living phenomena, the more complex they appear to be. The example involving human reasoning makes clear that the brain is still largely unknown territory. Like Einstein, who said he held ‘humble admiration of the illimitable superior spirit who reveals himself in the slight details we are able to perceive with our frail and feeble mind’, I have a deep admiration for the Architect who reveals himself in the details that we are privileged to study in our research. As Albert Einstein said: The important thing is not to stop questioning.Curiosity has its own reason for existing.
Keywords: Curiosity; scientific research; cosmology; perinatal research; ECG; human reasoning